A recycling method for ternary lithium-ion batteries

By using the battery itself to reduce materials and specific extractants during the recycling process of ternary lithium-ion batteries, efficient lithium leaching and separation of nickel, cobalt, manganese and copper, iron and aluminum are achieved, solving the problems of low lithium purity and difficulty in separation in the prior art, and improving the purity and economicality of the recycled products.

CN116253339BActive Publication Date: 2025-03-07HUNAN KEYKING RECYCLING TECH LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310136795.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-03-07
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

In the prior art, when recycling ternary lithium-ion batteries, the purity of lithium is not high, and it is difficult to effectively separate metals such as nickel, cobalt, manganese, and copper, iron and aluminum.

Method used

By calcining the broken ternary lithium-ion battery in an inert protective atmosphere, the reduction of the positive electrode material is achieved by grinding the iron, aluminum into powder and graphite in the battery itself, thereby efficiently leaching of lithium. At the same time, metals such as nickel, cobalt, manganese, copper, iron and aluminum are effectively separated and recovered by adjusting the pH value and using specific extractive agents.

Benefits of technology

The leaching rate of lithium reached 98.5%, the leaching rate of nickel, cobalt, manganese, and copper, iron and aluminum were effectively separated, improving the purity and economicality of the recycled products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a recovery method for a ternary lithium ion battery, which belongs to the field of batteries and comprises the following steps: crushing the battery and heating it for reaction, collecting the condensed electrolyte by negative pressure, obtaining solid materials and carrying out first-stage and second-stage roasting; leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite; removing impurities from the lithium solution, concentrating and crystallizing to obtain battery-grade lithium hydroxide; adding water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make pulp, and adding acid; adding iron powder to the solution to remove copper; extracting nickel and cobalt by HBL110, and then extracting by P204, and concentrating and crystallizing the solution to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride; adding sodium chlorate to the extracted residual solution after extraction to oxidize divalent iron into trivalent iron, and then adjusting with alkali, filtering to obtain slag containing iron lithium and a manganese solution containing calcium and magnesium; extracting manganese in the manganese solution by C272, obtaining manganese sulfate or manganese chloride solution after back extraction, and concentrating and crystallizing to obtain battery-grade manganese sulfate or manganese chloride for batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery manufacturing, and in particular relates to a method for recycling a ternary lithium-ion battery. Background Art

[0002] Ternary lithium-ion battery refers to a secondary lithium-ion battery that uses three nickel-cobalt-manganese transition metal oxides as positive electrode materials. It fully combines the good performance of lithium cobalt oxide cycle, the high specific capacity of lithium nickel oxide, and the high safety and low cost of lithium manganese oxide. It is a composite lithium intercalation oxide with multiple elements (such as cobalt and manganese) at the molecular level synthesized by mixing, doping, coating and surface modification of nickel. It is a rechargeable lithium-ion battery that has been widely studied and applied.

[0003] The life of a lithium-ion battery refers to the end of its service life when the battery capacity decomposes to 70% of the nominal capacity after a period of use. In industry, the cycle life is usually calculated by the number of cycles when the lithium-ion battery is fully charged and discharged. During use, irreversible electrochemical reactions will occur inside the lithium-ion battery, which will lead to a decrease in capacity, such as electrolyte breakdown, deactivation of active materials, collapse of the positive and negative electrode structures, and a decrease in the number of internal and external lithium ions. The theoretical life of a ternary lithium-ion battery is about 800 cycles, which is the average life in commercial rechargeable lithium-ion batteries. Used ternary lithium-ion batteries after use contain a variety of harmful substances, such as organic solvents, heavy metals and toxic gases. If they are not recycled, they will cause serious environmental pollution. The most valuable part of the recycling process of used ternary lithium-ion batteries is the recovery of metals such as nickel, cobalt, manganese, copper, iron and aluminum in lithium-ion batteries. At present, the existing technology can achieve the recovery of metals, but the purity of the final lithium product obtained is not high. Summary of the invention

[0004] The purpose of the present invention is to provide a method for recycling ternary lithium-ion batteries. The present invention utilizes the characteristics that the iron and aluminum of the battery itself are reducible after being ground into powder, and that graphite is reducible when burned under certain conditions to produce carbon monoxide. During the roasting process, the positive electrode material of the ternary lithium-ion battery is reduced, so that lithium can be selectively leached out with water at the front end. The leaching rate of lithium in this process is as high as 98.5%, and no reducing gas such as hydrogen is added. The slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite is adjusted to a pH value of 1.0-2.0 with sulfuric acid or hydrochloric acid, and the leaching rate of nickel, cobalt and manganese can reach 99.5%, while the leaching rate of copper, iron and aluminum is less than 10%. This method effectively separates nickel, cobalt and manganese from copper, iron and aluminum.

[0005] The present invention is achieved through the following technical solution: a method for recycling ternary lithium-ion batteries, comprising the following steps:

[0006] Step 1: crushing the ternary lithium-ion battery in an inert protective atmosphere to obtain crushed materials;

[0007] Step 2: placing the crushed material in a closed environment for heating and reaction, and collecting the condensed electrolyte by negative pressure to obtain a solid material;

[0008] Step 3: After ball milling, the solid material is passed through a 20-500 mesh sieve;

[0009] Step 4: performing primary and secondary roasting on the solid material of step 3;

[0010] Step 5: leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite;

[0011] Step 6: The lithium solution obtained in step 5 is purified by resin or membrane to obtain a pure lithium hydroxide solution, and the lithium hydroxide is concentrated and crystallized to obtain a battery-grade lithium hydroxide monohydrate product;

[0012] Step 7: Add water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make a slurry, add sulfuric acid or hydrochloric acid, adjust the pH value to be stable at 1.0-2.0 for 20-40 minutes, and filter to obtain graphite slag and solution;

[0013] Step 8: Add reduced iron powder to the solution to remove copper, and filter to obtain sponge copper and a solution after copper removal;

[0014] Step 9: extracting nickel and cobalt in the solution after copper removal with HBL110 extractant, and then stripping to obtain nickel cobalt sulfate solution or nickel cobalt chloride solution;

[0015] Step 10: extracting the nickel cobalt sulfate solution or the nickel cobalt chloride solution with P204, and then stripping the nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride solution, and concentrating and crystallizing the solution to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride;

[0016] Step 11: adding sodium chlorate to the extract residue after extraction in step 9 to oxidize the divalent iron in the extract residue to trivalent iron, and then adjusting the pH value of the extract residue after extraction in step 9 to 4.0-5.0 with sodium hydroxide, sodium carbonate or calcium carbonate, and filtering to obtain iron-lithium-containing slag and calcium-magnesium-containing manganese solution;

[0017] Step 12: extracting manganese from the manganese solution with C272 extractant, stripping to obtain manganese sulfate or manganese chloride solution, concentrating and crystallizing to obtain battery-grade manganese sulfate or battery-grade manganese chloride.

[0018] Preferably, in step 1, the positive electrode material of the ternary lithium-ion battery is LiNi x Co y Mn z O 2, where 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1.

[0019] Preferably, in step 2, the reaction temperature is 100-250°C.

[0020] Preferably, in step 4, the first stage calcination is performed at 300-400°C for 1-3h in an inert protective atmosphere, and the second stage calcination is performed at 750-1000°C for 20-60min in an air atmosphere.

[0021] Preferably, in step 7, the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite is slurried with water, and the solid-liquid ratio is 1:3-1:6.

[0022] Preferably, in step 8, reduced iron powder is added to the solution, the amount of iron powder added is 1.0-1.3 times the total amount of copper in the solution, and the copper content in the solution after copper removal is no more than 0.005 g / L.

[0023] Among them, the HBL110 extractant provides a solution for selective direct extraction of nickel from nickel-containing acidic solutions (latite nickel ore acid leaching solution, nickel-containing electroplating sludge acid leaching solution, nickel-containing waste catalyst acid leaching solution, etc.). In the extraction, separation and purification process of nickel-containing acidic solutions, HBL110 can selectively and directly extract nickel, and basically does not extract Fe, Al, Cr, Zn, Mn, Mg, Ca, etc., to achieve the separation of Ni from the above impurities, and replace the four processes of "precipitation to remove Fe, hydrolysis to remove Fe and Al, precipitation of Ni and Co, acid dissolution" in the traditional nickel wet treatment process with a single process of "direct extraction of Ni", which greatly shortens the process flow, significantly reduces costs, and greatly improves the yield of nickel, while realizing the comprehensive recycling of valuable metal resources.

[0024] Physical properties of HBL110 extractant: Appearance: brown transparent liquid; Specific gravity (25℃) 0.97±0.005g / cm 3 ; Flash point>70℃; Performance parameters: Maximum nickel loading ≥7g / L; Extraction kinetics ≥95% (5min); Extraction phase separation ≤5min; Stripping kinetics ≥90% (5min); Stripping phase separation ≤5min.

[0025] Among them, p204: Name: di(2-ethylhexyl) phosphate; di(2-ethylhexyl) phosphate; diisooctyl phosphate; dioctyl phosphate, national CAS registration number: 298-07-7, is a colorless, transparent and viscous liquid. The freezing point is -60℃, the relative density is 0.973 (25 / 25℃), the refractive index is 1.4420 (25℃), and the boiling point is 209℃ (1.33kPa).

[0026] Among them, the main component of C272 extractant is di(2,4,4-trimethylpentyl)phosphonic acid. Typical physical properties of industrial products: content>85%; colorless or slightly amber; density (24℃) is 0.92g / cm 3 Viscosity (25℃) 0.142Pa.s, (50℃) 0.037Pa.s; freezing point -32℃; flash point 108℃; solubility in water (PH=2.6) is 16ppm.

[0027] The present invention has the following beneficial effects:

[0028] 1. Taking advantage of the fact that the iron and aluminum in the battery itself are reducible after being ground into powder, and the fact that graphite burns under certain conditions to produce carbon monoxide, the positive electrode material of the ternary lithium-ion battery is reduced during the roasting process, so that lithium can be selectively leached out with water at the front end. The lithium leaching rate of this process is as high as 98.5%, and no external reducing gases such as hydrogen are required.

[0029] 2. The slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite is adjusted to pH 1.0-2.0 with sulfuric acid or hydrochloric acid. The leaching rate of nickel, cobalt and manganese can reach 99.5%, while the leaching rate of copper, iron and aluminum is less than 10%. This method can effectively separate nickel, cobalt and manganese from copper, iron and aluminum.

[0030] 3. Without removing iron, aluminum, calcium and magnesium, nickel and cobalt are directly extracted with HBL110 extractant, which reduces the loss of nickel and cobalt and improves the recovery rate of nickel and cobalt.

[0031] 4. Use C272 extractant to extract manganese from the manganese solution. The manganese sulfate or manganese chloride obtained after stripping does not need to be impurity-removed, and can be directly concentrated and crystallized to obtain battery-grade manganese sulfate or manganese chloride for batteries.

[0032] 5. The lithium hydroxide solution obtained after reduction can be used to prepare battery-grade lithium hydroxide monohydrate after removing impurities through resin or membrane. DETAILED DESCRIPTION

[0033] The following detailed description of the present application will make the features and advantages of the present application clearer and more explicit.

[0034] In the description of the present application, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "back", "left" and "right" indicate positions or positional relationships based on the working state of the present application, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third" and "fourth" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0035] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0036] Embodiment 1, the present invention is realized by the following technical scheme: a method for recycling ternary lithium-ion batteries, comprising the following steps:

[0037] Step 1: Crush the ternary lithium-ion battery in an inert protective atmosphere to obtain crushed materials; the ternary lithium-ion battery has a positive electrode material of LiNi x Co y Mn z O 2 (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1);

[0038] Step 2: placing the crushed material in a closed environment for heating reaction, collecting the condensed electrolyte by negative pressure to obtain a solid material, and the reaction temperature is 250° C.;

[0039] Step 3: After ball milling, the solid material is passed through a 500-mesh sieve;

[0040] Step 4: calcining at 400°C for 3h in an inert protective atmosphere, and calcining at 1000°C for 60min in an air atmosphere;

[0041] Step 5: leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite;

[0042] Step 6: The lithium solution obtained in step 5 is purified by resin or membrane to obtain a pure lithium hydroxide solution, and the lithium hydroxide is concentrated and crystallized to obtain a battery-grade lithium hydroxide monohydrate product.

[0043] Step 7: Add water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make slurry with a solid-liquid ratio of 1:6, add sulfuric acid or hydrochloric acid, adjust the pH value to be stable at 2.0 for 40 minutes, and filter to obtain graphite slag and solution.

[0044] Step 8: adding reduced iron powder to the solution, wherein the amount of iron powder added is 1.3 times the total amount of copper in the solution, and the copper content in the solution after copper removal is not more than 0.005 g / L, and filtering to obtain sponge copper and a solution after copper removal;

[0045] Step 9: extracting nickel and cobalt in the solution after copper removal with HBL110 extractant, and then stripping to obtain nickel cobalt sulfate solution or nickel cobalt chloride solution;

[0046] Step 10: The nickel cobalt sulfate solution or the nickel cobalt chloride solution is extracted with P204, and then the nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride solution is stripped, and the solution is concentrated and crystallized to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride.

[0047] Step 11: adding sodium chlorate to the extract residue after extraction in step 9 to oxidize the divalent iron in the extract residue to trivalent iron, and then adjusting the pH value of the extract residue after extraction in step 9 to 5.0 with sodium hydroxide, sodium carbonate or calcium carbonate, and filtering to obtain iron-lithium-containing slag and calcium-magnesium-containing manganese solution.

[0048] Step 12: extracting manganese from the manganese solution with C272 extractant, stripping to obtain manganese sulfate or manganese chloride solution, concentrating and crystallizing to obtain battery-grade manganese sulfate or battery-grade manganese chloride.

[0049] Embodiment 2, the present invention is realized by the following technical scheme: a method for recycling ternary lithium-ion batteries, comprising the following steps:

[0050] Step 1: Crush the ternary lithium-ion battery in an inert protective atmosphere to obtain crushed materials; the ternary lithium-ion battery has a positive electrode material of LiNi x Co y Mn z O 2 (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1);

[0051] Step 2: placing the crushed material in a closed environment for heating reaction, collecting the condensed electrolyte by negative pressure to obtain a solid material, and the reaction temperature is 100° C.;

[0052] Step 3: After ball milling, the solid material is passed through a 20-mesh sieve;

[0053] Step 4: calcining at 300°C for 1 hour in an inert protective atmosphere, and calcining at 750°C for 20 minutes in an air atmosphere;

[0054] Step 5: leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite;

[0055] Step 6: The lithium solution obtained in step 5 is purified by resin or membrane to obtain a pure lithium hydroxide solution, and the lithium hydroxide is concentrated and crystallized to obtain a battery-grade lithium hydroxide monohydrate product.

[0056] Step 7: Add water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make slurry with a solid-liquid ratio of 1:3, add sulfuric acid or hydrochloric acid, adjust the pH value to be stable at 1.0 for 20 minutes, and filter to obtain graphite slag and solution.

[0057] Step 8: adding reduced iron powder to the solution, wherein the amount of iron powder added is 1.0 times the total amount of copper in the solution, and the copper content in the solution after copper removal is not more than 0.005 g / L, and filtering to obtain sponge copper and a solution after copper removal;

[0058] Step 9: extracting nickel and cobalt in the solution after copper removal with HBL110 extractant, and then stripping to obtain nickel cobalt sulfate solution or nickel cobalt chloride solution;

[0059] Step 10: The nickel cobalt sulfate solution or the nickel cobalt chloride solution is extracted with P204, and then the nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride solution is stripped, and the solution is concentrated and crystallized to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride.

[0060] Step 11: adding sodium chlorate to the extract residue after extraction in step 9 to oxidize the divalent iron in the extract residue to trivalent iron, and then adjusting the pH value of the extract residue after extraction in step 9 to 4.0 with sodium hydroxide, sodium carbonate or calcium carbonate, and filtering to obtain iron-lithium-containing slag and calcium-magnesium-containing manganese solution.

[0061] Step 12: extracting manganese from the manganese solution with C272 extractant, stripping to obtain manganese sulfate or manganese chloride solution, concentrating and crystallizing to obtain battery-grade manganese sulfate or battery-grade manganese chloride.

[0062] Embodiment 3, the present invention is realized by the following technical scheme: a method for recycling ternary lithium-ion batteries, comprising the following steps:

[0063] Step 1: Crush the ternary lithium-ion battery in an inert protective atmosphere to obtain crushed materials; the ternary lithium-ion battery has a positive electrode material of LiNi x Co y Mn z O 2 (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1);

[0064] Step 2: placing the crushed material in a closed environment for heating reaction, collecting the condensed electrolyte by negative pressure to obtain a solid material, and the reaction temperature is 200° C.;

[0065] Step 3: After ball milling, the solid material is passed through a 300-mesh sieve;

[0066] Step 4: calcining at 350°C for 2h in an inert protective atmosphere, and calcining at 800°C for 40min in an air atmosphere;

[0067] Step 5: leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite;

[0068] Step 6: The lithium solution obtained in step 5 is purified by resin or membrane to obtain a pure lithium hydroxide solution, and the lithium hydroxide is concentrated and crystallized to obtain a battery-grade lithium hydroxide monohydrate product.

[0069] Step 7: Add water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make slurry with a solid-liquid ratio of 1:5, add sulfuric acid or hydrochloric acid, adjust the pH value to be stable at 1.5 for 30 minutes, and filter to obtain graphite slag and solution.

[0070] Step 8: adding reduced iron powder to the solution, wherein the amount of iron powder added is 1.2 times the total amount of copper in the solution, and the copper content in the solution after copper removal is not more than 0.005 g / L, and filtering to obtain sponge copper and a solution after copper removal;

[0071] Step 9: extracting nickel and cobalt in the solution after copper removal with HBL110 extractant, and then stripping to obtain nickel cobalt sulfate solution or nickel cobalt chloride solution;

[0072] Step 10: The nickel cobalt sulfate solution or the nickel cobalt chloride solution is extracted with P204, and then the nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride solution is stripped, and the solution is concentrated and crystallized to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride.

[0073] Step 11: adding sodium chlorate to the extract residue after extraction in step 9 to oxidize the divalent iron in the extract residue to trivalent iron, and then adjusting the pH value of the extract residue after extraction in step 9 to 4.5 with sodium hydroxide, sodium carbonate or calcium carbonate, and filtering to obtain iron-lithium-containing slag and calcium-magnesium-containing manganese solution.

[0074] Step 12: extracting manganese from the manganese solution with C272 extractant, stripping to obtain manganese sulfate or manganese chloride solution, concentrating and crystallizing to obtain battery-grade manganese sulfate or battery-grade manganese chloride.

[0075] The present application is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, a variety of equivalent replacements, modifications or improvements can be made to the technical solution of the present application and its implementation methods, all of which fall within the scope of the present application. The scope of protection of the present application shall be subject to the attached claims.

Claims

1. A method for recycling ternary lithium-ion batteries, characterized in that: The following steps are involved: Step 1: crushing the ternary lithium-ion battery in an inert protective atmosphere to obtain crushed materials; Step 2: placing the crushed material in a closed environment for heating and reaction, and collecting the condensed electrolyte by negative pressure to obtain a solid material; Step 3: After ball milling, the solid material is passed through a 20-500 mesh sieve; Step 4: The solid material of step 3 is subjected to primary and secondary calcination, wherein the primary calcination is carried out at 300-400° C. for 1-3 h in an inert protective atmosphere, and the secondary calcination is carried out at 750-1000° C. for 20-60 min in an air atmosphere; Step 5: leaching with water and filtering to obtain a lithium solution and slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite; Step 6: The lithium solution obtained in step 5 is purified by resin or membrane to obtain a pure lithium hydroxide solution, and the lithium hydroxide is concentrated and crystallized to obtain a battery-grade lithium hydroxide monohydrate product; Step 7: Add water to the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite to make a slurry, add sulfuric acid or hydrochloric acid, adjust the pH value to be stable at 1.0-2.0 for 20-40 minutes, and filter to obtain graphite slag and solution; Step 8: Add reduced iron powder to the solution to remove copper, and filter to obtain sponge copper and a solution after copper removal; Step 9: extracting nickel and cobalt in the solution after copper removal with HBL110 extractant, and then stripping to obtain nickel cobalt sulfate solution or nickel cobalt chloride solution; Step 10: extracting the nickel cobalt sulfate solution or the nickel cobalt chloride solution with P204, and then stripping the nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride solution, and concentrating and crystallizing the solution to obtain refined nickel sulfate, cobalt sulfate or nickel chloride, cobalt chloride; Step 11: adding sodium chlorate to the extract residue after extraction in step 9 to oxidize the divalent iron in the extract residue to trivalent iron, and then adjusting the pH value of the extract residue after extraction in step 9 to 4.0-5.0 with sodium hydroxide, sodium carbonate or calcium carbonate, and filtering to obtain iron-lithium-containing slag and calcium-magnesium-containing manganese solution; Step 12: extracting manganese from the manganese solution with C272 extractant, stripping to obtain manganese sulfate or manganese chloride solution, concentrating and crystallizing to obtain battery-grade manganese sulfate or battery-grade manganese chloride.

2. The method for recycling a ternary lithium-ion battery according to claim 1, characterized in that: In step 1, the positive electrode material of the ternary lithium-ion battery is LiNi x Co y Mn z O2, where 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1.

3. The method for recycling a ternary lithium-ion battery according to claim 1, characterized in that: In step 2, the reaction temperature is 100-250°C.

4. The method for recycling a ternary lithium-ion battery according to claim 1, characterized in that: In step 7, the slag containing nickel, cobalt, manganese, copper, iron, aluminum and graphite is slurried with water, and the solid-liquid ratio is 1:3-1:

6.

5. The method for recycling a ternary lithium-ion battery according to claim 1, characterized in that: In step 8, reduced iron powder is added to the solution, and the amount of iron powder added is 1.0-1.3 times the total amount of copper in the solution. After copper removal, the copper content in the solution is not more than 0.005 g / L.

Citation Information

Patent Citations

  • Method for recovering and purifying nickel cobalt from manganese-containing waste material

    CN106904667A

  • Method for preparing lithium carbonate and ternary precursor by recycling waste ternary lithium battery

    CN112374511A

  • Recycling method of waste nickel-cobalt-manganese-lithium battery

    CN114039120A